(untitled) (Al-Farooq Journal of Sciences, 2026)
This empirical study examines the impact of Human Resource Management (HRM) practices—specifically spatial planning and recruitment, training and development, performance appraisal, and developmental incentives—on achieving organizational sustainability across its economic, social, and environmental/spatial dimensions. Framed within the geography of human resources development, which emphasizes spatial distribution, regional disparity, and sustainable workforce utilization, a structured questionnaire was designed and distributed to an administrative and academic sample. Utilizing descriptive and inferential statistical techniques via SPSS, including multiple regression analysis, the empirical results indicated a statistically significant positive effect of HRM practices on organizational sustainability at (α ≤ 0.05). Furthermore, considering spatial geography in workforce distribution substantially reduced regional development gaps and enhanced operational efficiency. Practical recommendations are formulated for policymakers and strategic human resource planners.